British Thoracic Society quality standards for home oxygen use in adults. Issue 1 (18th September 2017) - Suntharalingam, Jay; Wilkinson, Tom; Annandale, Joseph; Davey, Claire; Fielding, Rhea; Freeman, Daryl; Gibbons, Michael; Hardinge, Maxine; Hippolyte, Sabrine; Knowles, Vikki; Lee, Cassandra; MacNee, William; et al.
Abstract : Introduction: The purpose of the quality standards document is to provide healthcare professionals, commissioners, service providers and patients with a guide to standards of care that should be met for home oxygen provision in the UK, together with measurable markers of good practice. Quality statements are based on the British Thoracic Society (BTS) Guideline for Home Oxygen Use in Adults. Methods: Development of BTS Quality Standards follows the BTS process of quality standard production based on the National Institute for Health and Care Excellence process manual for the development of quality standards. Results: 10 quality statements have been developed, each describing a key marker of high-quality, cost-effective care for home oxygen use, and each statement is supported by quality measures that aim to improve the structure, process and outcomes of healthcare. Discussion: BTS Quality Standards for home oxygen use in adults form a key part of the range of supporting materials that the society produces to assist in the dissemination and implementation of a guideline's recommendations.